A technical-economic analysis of turbine inlet air cooling for a heavy duty gas turbine operating with blast-furnace gas (Research, Society and Development, 2021)
The study was developed inside an integrated steel mill, located in Rio de Janeiro city, aiming to analyse the technical-economic feasibility of installing a new inlet air refrigeration system for the gas turbines. The technologies applied for such purpose are named Turbine Inlet Air Cooling (TIAC) technologies. The power plant utilizes High Fogging and Evaporative Cooling methods for reducing the compressor’s inlet air temperature, however, the ambient climate condition hampers the turbine’s power output when considering its design operation values. Hence, this study was proposed to analyse the installation of an additional cooling system. The abovementioned power plant has two heavy-duty gas turbines and one steam turbine, connected in a combined cycle configuration. The cycle nominal power generation capacity is 450 MW with each of the gas turbines responsible for 90 MW. The gas turbines operate with steelwork gases, mainly blast furnace gas (BFG), and natural gas. The plant has its own weather station, which provided significant and precise data regarding the local climate conditions over the year of 2017. An in-house computer model was created to simulate the gas turbine power generation and fuel consumption considering both cases: with the proposed TIAC system and without it, allowing the evaluation of the power output increase due to the new refrigeration system. The results point out for improvements of 4.22% on the power output, corresponding to the electricity demand of approximately 32960 Brazilian homes per month or yearly earnings of 3.92 million USD.